A Radar and Sonar-Based Hybrid Forefield Reconnaissance System for Melting Probes for Englacial Exploration - Stelzig, Michael; Haberberger, Niklas; Audehm, Jan; Becker, Fabian; Nghê, Chi Thanh; Ellinger, Enrico; Do, Mia; Krabbe, Lena; Heinen, Dirk; Zierke, Simon; Böck, Georg; Helbing, Klaus; et al. (IEEE Transactions on Geoscience and Remote Sensing, 2024)
The polar regions of Mars as well as the ice-covered moons such as Saturn’s Enceladus and Jupiter’s Europa have emerged as significant targets for ongoing and future space missions focused on investigating potentially habitable celestial bodies within our solar system. A key objective of these missions is to explore subglacial water reservoirs lying beneath the ice crusts of moons, such as Europa. The utilization of melting probes shows immense promise for achieving this goal. However, in addition to the capability to melt through the ice body, such a probe must also be able to identify the ice–water interface as well as obstacles in its path, such as cavities or meteoric rocks. To address these challenges, we present a forefield reconnaissance system (FRS) featuring a hybrid sensing approach that combines radar and sonar both integrated into the tip of a melting probe. Furthermore, the system includes an in situ permittivity sensor to ensure accurate radar range assignment and to gather scientific data about the ice body. The system has been integrated into a demonstrator melting probe and tested in a terrestrial analog scenario. Measurements at the Jungfraufirn in Switzerland confirm the potential of the developed system.<br
Keywords: Probes; Radar; Reservoirs; Sonar; Heating systems; Snow; Permittivity; Radar System; Solar System; Thermal Conductivity; Dielectric Constant; Autonomous Vehicles; Acoustic Signals; Inertial Measurement Unit; Vector Network Analyzer; Phase-locked Loop; Simultaneous Localization And Mapping; Planar Antenna; Gallium Nitride; Robot Operating System; Ground Penetrating Radar; Aluminum Nitride; Coaxial Line; German Aerospace Center; High Power Amplifier; Protection Circuit; Outer Conductor; Relative Permittivity Values; Acoustic Transducer; Extraterrestrial Life; Binary Phase Shift Keying; Stray Field; Echo Signal; Test Locations; Antenna Array; Radar Measurements; Equivalent Circuit